Extent of Substance Abuse among Secondary School Students In Nsukka Local Government Area, Enugu State - Ene, Osmond C.; Ochiaka, Raphael E. (International Journal of Human Kinetics, Health and Education, 2023)
The study aimed at investigating the extent of substance abuse among secondary school students in Nsukka Local Government Area of Enugu State. Cross-sectional survey research design was adopted for the study. A sample of 391 students was drawn using multi-stage sampling procedure from a population of 10,513secondary school students in 21 public secondary schools in Nsukka Local Government Area.A29-item scale titled ‘Extent of Substance Abuse Questionnaire’ (ESAQ)developed by the researcher was the instrument used for data collection. The questionnaire was validated by three experts, and Cronbach’s Alpha statistic was used to ascertain reliability of the instrument which yielded a co-efficient value of 0.75 adjudged reliable for the study. Mean and percentages were used to analyse and answer the research questions while the hypothesis was tested using t-test at .05 level of significance. Results among others showed, that the substances students commonly abused are alcohol, tobacco and marijuana, Male and female students highly abused alcohol while male students only highly abused tobacco and marijuana, and that, peer pressure and to keep awake are the major factors that contribute to substance abuse. Findings also showed that substance abuse is dependent on gender. Based on the findings, recommendations were made among which is, qualified health educators should be employed in every secondary school in Enugu State to teach health education with emphasis on substance abuse and its implications.